Hope rises - Baldacci, David (Walter Nash series, 2026)
"Walter Nash, working under the alias of Dillon Hope, is on the road to revenge after becoming an informant for the FBI against a global criminal operation headed up by Victoria Steers. Steers has ripped everything Nash held dear away from him. He has nothing left to lose and with long, rigorous training under his belt the gentle and sensitive Nash has transformed into something he never thought he'd be: a physically imposing man with lethal skills. And now he has only goal left in life: taking down Victoria Steers. In order to succeed, he's going to need to cross enemy lines and work the job from the inside. But Steers is shrewd and only brings those with her complete trust into her inner circle. Nash must rely on every ounce of his hard-earned skills in order to prove himself an ally to Steers if he's ever going to get close enough to decimate her criminal empire. Yet, despite hating the woman for destroying his life, Nash finds himself oddly drawn to Steers in ways that he never could've imagined. And what he ultimately discovers will turn all he believed upside down, forcing Nash to do something truly unfathomable. So, will the truth set Nash free? Or end him?" --